CORRELATION ANALYSIS OF THE HISTOMORPHOLOGICAL SPECTRUM OF TUBERCULOUS GRANULOMATOUS INFLAMMATION WITH ACID-FAST BACILLI DENSITY: ANALISIS KORELASI SPEKTRUM HISTOMORFOLOGI RADANG GRANULOMATOSA TUBERKULOSIS DENGAN KEPADATAN INFILTRASI ACID-FAST BACILLI - Delyuzar; Betty; T Kemala Intan; Arie Widiansyah Hasibuan (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
The histomorphological spectrum of tuberculous granulomatous inflammation is considered to reflect bacillary replication dynamics and the host immune response. This analytic observational cross-sectional study was conducted retrospectively by reviewing secondary medical records and archived histopathology slides and paraffin blocks to assess the correlation and strength of association between tuberculous granulomatous histomorphology on Hematoxylin–Eosin staining and acid-fast bacilli (AFB) density on Modified Ziehl–Neelsen staining at the Unit Patologi Anatomik Rumah Sakit Pendidikan Prof. dr. Chairuddin Panusunan Lubis USU Medan and Rumah Sakit Columbia Asia Medan during 2023–2025, using consecutive sampling; 68 cases met the inclusion criteria. Histomorphology was categorized into epithelioid granuloma with or without Langhans-type giant cells with a necrotic mass, epithelioid granuloma with or without Langhans-type giant cells without necrosis, and acellular eosinophilic mass with inflammatory cells. AFB density was graded semi-quantitatively (0, +1, +2, +3) at 1000× magnification. Statistical analysis was performed using Fisher-Freeman-Halton exact test and Cramer’s V. Most cases were extrapulmonary (95.59%), demonstrated epithelioid granuloma with necrosis (69.12%), and showed an AFB score of +1 (67.65%). Histomorphology showed a significant correlation with AFB density (p<0.001) with a strong association (Cramer’s V=0.59), whereas correlations with organ group, age, and sex were not significant (p>0.05).